SHOULDER JOINT PAIN: APPROACHES TO DIAGNOSIS AND TREATMENT - N. A. Shostak; A. A. Klimenko (Klinicist, 2014)
The paper presents main approaches to the differential diagnosis of shoulder joint pathology and describes the major nosological entities of shoulder diseases. It gives data on the possibility of using nanotechnologies in optimizing the management of a patient with chronic shoulder joint pain syndrome.